Mafhūm Khalq al-‘Ālam inda Badī’uzzamān Sa’īd al-Nūrsī : The Concept of Nature Creation according to Badi'uzzaman Sa'id Nursi - Achmad Reza Hutama Al Faruqi; Muhammad Arief; Muhammad Hadi Wannes (University of Darussalam Gontor, Indonesia, 2023)
This article aims to explain Said Nursi's thoughts on the Creation of Nature and criticism of the views of naturalist philosophers. In his work, Risalah Nur tries to reveal the concept of the Creation of Nature According to Bediuzzaman Said Nursi (based on his criticism of the philosophy of Naturalism). To build this works, the authors use a philosophical approach with descriptive and analytical methods in his concept of the Creation of Nature with his logical thinking so that it can be a critique of the concept of Naturalism. Analyze the data by describing Nursi’s thoughts and analyzing them both by comparing and contrasting with the thougths of other figures in muslim philosophy and Naturalism. In his study on the creation of nature, as a paradigm Nursi used philosophy method in his critique of the philosophy of Naturalism. Bediuzzaman stated that in fact Nature was Allah’s creation, as this proved the testimony of the facts presented in Islam to mankind in humans and objects in this nature. The essence of the nature creation is to reflect or prove the existence of God. The positions of God as an existence that controls and creates nature. which is contrary to the philosophical understanding of Naturalism which assumes that nature was created by itself or without the God.